The time varying drivers of net capital flows around an oil price shock (2018)
This paper aims to identify the main drivers of net capital flows for some petroleum exporting countries in South America and Asia, and to analyze how their relative relevance changed around the 2014-2016 oil prices fall. This characterization discriminates between pull and push factors, finding that both drivers are relevant to define the volume and dynamics of net capital flows. In particular, global liquidity, global risk aversion, oil prices and US equity returns are the main push factors; while economic growth, interest rates differentials, sovereign risk and domestic equity returns are the main pull factors. The time varying nature of the determinants is modeled with Bayesian estimation methods finding that the relevance of some factors changed during the oil prices fall. This result highlights the dynamic nature of net capital flows and the importance of having enough buffers to deal with their volatilities.